2020
DOI: 10.1182/blood.2019004560
|View full text |Cite
|
Sign up to set email alerts
|

Mutational and phenotypic characterization of hereditary hemorrhagic telangiectasia

Abstract: Hereditary hemorrhagic telangiectasia (HHT) is a vascular dysplasia inherited as an autosomal dominant trait. Care delivery is impeded by requirements for laborious, repeated phenotyping, and gaps in knowledge regarding the relationships between causal DNA variants in ENG, ACVRL1, SMAD4 and GDF2, and clinical manifestations. To address, we analysed DNA samples from 183 previously uncharacterised, unrelated HHT and suspected HHT cases using the ThromboGenomics high-throughput sequencing platform. We identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(97 citation statements)
references
References 78 publications
(130 reference statements)
0
94
0
3
Order By: Relevance
“…The product of this gene forms homomeric complexes and heteromeric complexes with other activated Smad proteins in the context of activating by TGF-β receptors, then accumulate in the nucleus and regulate the transcription of target genes [ 4 ]. Mutations or deletions in the SMAD4 gene have been shown to result in pancreatic cancer [ 5 ], juvenile polyposis syndrome [ 6 ], and hereditary hemorrhagic telangiectasia [ 7 ]. In the past 2 decades, many studies had shown that SMAD4 mutation can not cause tumorigenesis by itself, but it can promote tumor progression caused by other genes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The product of this gene forms homomeric complexes and heteromeric complexes with other activated Smad proteins in the context of activating by TGF-β receptors, then accumulate in the nucleus and regulate the transcription of target genes [ 4 ]. Mutations or deletions in the SMAD4 gene have been shown to result in pancreatic cancer [ 5 ], juvenile polyposis syndrome [ 6 ], and hereditary hemorrhagic telangiectasia [ 7 ]. In the past 2 decades, many studies had shown that SMAD4 mutation can not cause tumorigenesis by itself, but it can promote tumor progression caused by other genes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Study strengths include highlighting the landscape of genetic variation relevant to SARS-CoV-2, and questioning how strictly putative COVID-19 risk and protective alleles should be defined, particularly if they may become part of public health policies, as for underlying health conditions [25,26]. The pattern from Mendelian disorders was of over-exuberant pathogenicity calls in early research reports, with pathogenicity classifications of many variants later downgraded as assignments became increasingly stringent [14,28]. As a result, high proportion of coding variants in known disease-causing genes are currently clinically non-actionable due to classification as a VUS.…”
Section: Discussionmentioning
confidence: 99%
“…As described for the wider cohort,[7,16,20,53,54] all individuals reviewed in the clinical service were assessed using standardised methods including a detailed clinical history specifically focusing on aspects of the HHT phenotypes, and any disproportionate or unexpected symptomatic manifestations. Standardised hematological and biochemical assessments were performed using the hospital service laboratories as described.…”
Section: Methodsmentioning
confidence: 99%
“…[2-4] Estimated to affect approximately 1.5 million individuals worldwide,[5,6] HHT usually results from a heterozygous loss-of-function allele in ENG, ACVRL1 or SMAD4 , and is inherited as an autosomal dominant trait. [7] Haploinsufficiency at one of these loci predisposes to the development of abnormal vascular structures, especially arteriovenous malformations (AVMs) characterised by turbulent flow and defective vascular walls predisposing to hemorrhage. [8] Affected individuals experience spontaneous, recurrent nosebleeds due to abnormal nasal vasculature, and exhibit small visible telangiectatic vessels that tend to develop on the lips, oral cavity, and finger pads.…”
Section: Introductionmentioning
confidence: 99%